2021
DOI: 10.3390/info12010045
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Tourism in the Perception of Romanian Tourists: A Case Study of the Rodna Mountains National Park

Abstract: As a country, Romania tries to communicate abroad its authenticity, intact nature and unique cultural heritage. This message matches perfectly the main attributes associated to Rodna Mountains National Park, as it is the second national park in Romanian. The aim of the research is to identify and analyze the prospects for sustainable development of rural tourism in the area of Rodna Mountains National Park, taking into account its impact on the social and economic life of the inhabitants of the Rodna commune, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…˙Ilke Başarangil's research revealed a significant relationship between "satisfaction" in creative parks and "perceived service quality" and "behavioral intent" [77]. Research can clarify visitors' needs and opinions about the sustainability of a site in terms of visitor perceptions, which can then inform future planning and management [78]. Tourism destinations can improve their appeal, visitor experiences, and positive feedback loops by soliciting and utilizing visitor feedback.…”
Section: Tourist Experience and Satisfactionmentioning
confidence: 99%
“…˙Ilke Başarangil's research revealed a significant relationship between "satisfaction" in creative parks and "perceived service quality" and "behavioral intent" [77]. Research can clarify visitors' needs and opinions about the sustainability of a site in terms of visitor perceptions, which can then inform future planning and management [78]. Tourism destinations can improve their appeal, visitor experiences, and positive feedback loops by soliciting and utilizing visitor feedback.…”
Section: Tourist Experience and Satisfactionmentioning
confidence: 99%
“…Although not focused solely on the local communities, some of the articles included in this section have potential implications for them. To achieve an integrated approach to park resources, Cozma et al [44] analysed the impact of tourism on communities surrounding the parks. Çetinkaya et al [76] tried to understand the potential difficulties of local people using park areas as tourists.…”
Section: No Of Published Papersmentioning
confidence: 99%
“…With TOWS matrix analysis, cultural and creative parks can identify opportunities, threats, strengths, and weaknesses, formulating corresponding strategies and policies based on the analysis results [62]. In terms of visitor cognition, research can elucidate visitors' views and needs regarding park sustainability, thus guiding park planning and management [63,64]. Self-consistency research can reveal the synergistic effects of cultural and creative parks in ecological conservation and economic development, ensuring comprehensive park benefits [65].…”
Section: Evaluation Models For Cultural and Creative Parksmentioning
confidence: 99%